The Values of Character Education in the Poem "Tears of Lamentation" by Ibn Rumi - Rizzaldy Satria Wiwaha; Fitma Nailurrahmi; Hilma Auliya Fauziyatullah; Abdul Malik Qimanullah (al-Afkar, Journal For Islamic Studies, 2026)
The existence and role of Arabic literature in world civilization cannot be denied, particularly from the perspective of scholars. This is because Arabic literature has significantly contributed to the development of modern civilization. This study aims to analyze the meaning and sorrow in Ibn Rumi's elegy, explore the character education values embedded within it, and examine the linguistic style used to express his grief. This research employs a qualitative approach using the library research method, involving the review of various books, journals, and other publications related to the research topic. The findings reveal that the poet's life events influenced the emotional expression in his elegy, enhancing the beauty of the language style used.